Leaving Russia’s Backyard: GUAM and the Challenge of Integration - Schulze, Dana (TESTINSTANZ: Wissenschaftliche Schriften der Universität Münster, 2016)
The Organisation for Democracy and Economic Development–GUAM extends from the Black Sea region to the Caspian Sea and is situated between the European and the Russian integration project. The post-Soviet region has been scarcely studied by Western scholars of regionalism. Previous research concentrated primarily on the Commonwealth of Independent States (CIS). GUAM has not been initiated by Russia and its members are keen on getting involved in Western integration projects.In this book, the author explores the emergence and state of GUAM and constructs the wish to enhance development and to strengthen sovereignty as the two major integration motives of its member states Azerbaijan, Georgia, Moldova and Ukraine. Added to this, the analysis delivers explanations for the shortcomings of GUAM.This book revisits regional integration as an instrument to prosperity and independence for young and less developed states and provides many insights into the politics and economy of GUAM members. Permalink https://nbn-resolving.de/urn:nbn:de:hbz:6-56269419858ISBN978-3-8405-0130-2Paperback, XIV, 334 Seiten